The Impact of Bacteria and Biostimulants on Crude Oil Breakdown in Loamy Soil - Ekperi Nelson Ibezim; Uku Eruni Philip (International Journal of Pollution: Prevention & Control, 2025)
This study investigates the influence of bacteria and biostimulants—specifically Bryophyllum pinnatum leaves soaked in both water and ethanol—on the degradation of crude oil in loamy soil. A laboratory-scale bioremediation setup was employed using a batch reactor model and first-order degradation kinetics to assess total petroleum hydrocarbon (TPH) breakdown under controlled conditions. Various analytical tools and procedures, including gas chromatography (Agilent 6890) and microbial media such as nutrient agar and mineral salt agar, were utilized to monitor microbial growth, activity, and degradation rates throughout the experimental period. The results revealed that both bacterial and fungal populations increased significantly in response to the applied biostimulants, with ethanol-based treatments consistently yielding higher degradation rates and microbial counts than their water-based counterparts. Peak microbial activity was observed between 28 and 35 days, demonstrating that both biostimulant dosage and exposure duration are critical factors influencing microbial degradation performance and hydrocarbon breakdown efficiency. The study confirms that Bryophyllum pinnatum acts as an effective and sustainable natural biostimulant by supplying essential organic nutrients, vitamins, and growth-promoting compounds that stimulate microbial colonization and metabolic activity in crude oil–contaminated soil. Application of the first-order kinetic model enabled accurate prediction of TPH reduction over time and established a strong correlation between experimental and theoretical data. Overall, the findings highlight the potential of natural, plant-based amendments to enhance bioremediation efficiency, particularly in loamy and clayey soils affected by hydrocarbon contamination, and emphasize their sustainable role as eco-friendly alternatives to chemical remediation methods.
Keywords: Bryophylum pinnatum; bioremediation; biostimulants; first-order kinetics; total petroleum hydrocarbon (TPH)